Cloning of RNase L inhibitor (RLI) / Bibi Norazilah Azuratmi - Azuratmi, Bibi Norazilah (2009)
The RNase L inhibitor (RLI) is a new type of endoribonuclease inhibitor. RLI cDNA codes for a 68-kDa polypeptide which expression is not regulated by interferon (IFN). Its expression antagonizes the 2-5A binding ability and the nuclease activity of the endogenous RNase L. RLI does not lead to 2-5A degradation or to irreversible modification of RNase L. The aim of this study is to clone and express RLI in E. coli. The RT-PCR method was used to amplify the RLI. A set of primers have been designed to produce the target sequence. Few parameters were adjusted to optimize the RT-PCR for specificity and reproducibility. However due to time constraint, this study fails to amplify and clone the RLI in the E. coli.